"Unidade na diversidade, unidade na adversidade": a Igreja Episcopal Anglicana do Brasil e as múltiplas identidades do anglicanismo no século XXI. - Costa, Rafael Vilaça Epifani (2021)
The Anglican Episcopal Church of Brazil (IEAB) is a Christian denomination that covers the entire Brazilian territory. In the context of worldwide Anglicanism, it is the 19th Province of the Anglican Communion. Its foundation dates back to 1890, when missionaries from the Episcopal Church of the United States established the first Portuguese-speaking communities in the South of the country. Its history was also marked by the presence of English chaplaincies, since the 19th century, and by the work developed among Japanese immigrants in the beginning of the 20th century. Since the autonomy, in 1965, the Brazilian Province has undergone several changes, from its administrative structure to its theological, liturgical and ecclesiological positions. The proposal of this research was about how the Anglican Episcopal Church of Brazil built and consolidated its ecclesial identity, molding itself as a “liberal, inclusive, and in continuous reform” institution, in accordance with the Anglican ethos. The research was divided into five parts: the History of Anglicanism in Brazil and in the world; a case study on the Anglican Diocese of Recife; an analysis of the construction of the multiple identities of the IEAB; the 2018 General Synod; and the tensions, disputes and resignifications around the idea of what the Anglican identity would be. Based on a bibliographical review – with texts written by Brazilian and foreign researchers and documents from the Church and the Anglican Community –, this work sought to analyze how the concept of “Unity in Diversity” is related to the theme of Inclusiveness, that has been dividing the Anglican Communion in contemporary times. The thesis defended is that: the Brazilian Province shaped its multiple identities based on four theological emphases: The insertion of the Church in political and social issues, influenced by currents such as the Social Gospel and Liberation Theology; the Liturgical Inclusivity, with the new Book of Common Prayer, published in 2015; the Ordination of Women, approved in 1985, and consolidated with the election of the first female bishop in 2018; and the full inclusion of LGBT+ people in the sacramental life of the Church, with the acceptance of their ordination to the priesthood and the approval of same-sex marriage, during IEAB’s General Synod of 2018. As a result, a true “radiography” of the Anglican Episcopal Church of Brazil was developed, through an original research in the area of Religious Studies and Theology.